Analysis Of The Competitiveness Of Indonesian Coffee Exports In The International Market And The Factors That Affect It - Ahmad Nidhom Mahyuddin; Arief Bachtiar (International Journal of Economics, Business and Innovation Research, 2024)
Foreign trade provides a great opportunity to improve economic prosperity by maximizing the potential of the country's resources. Indonesia, as one of the world's largest coffee producers and exporters, faces a decline in coffee competitiveness which is reflected in volatile and declining exports. This study aims to analyze the influence of coffee production, international coffee prices, rupiah exchange rate, and land area on the competitiveness of Indonesia's coffee exports. The research was conducted over a period of 33 years (1990-2022) using the Revealed Comparative Advantage (RCA) Model, Error Correction Model (ECM), and multiple linear analysis using the Ordinary Least Squares (OLS) method. The results showed that coffee production had a significant influence in the short term, but not significantly in the long term. International coffee prices and the rupiah exchange rate have a significant negative effect in the long term, while not significant in the short term. Land area has a significant positive effect in the long term, but significant negative in the short term.